ANALISIS KESALAHAN BERBAHASA DALAM SURAT KABAR ONLINE SUARA MERDEKA EDISI 11 OKTOBER 2024 - Prissilia Prahesta Waningyun; Ngazizatun Ma’rifah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to identify errors in the use of language related to spelling, morphology, syntax, and semantics in the Suara Merdeka newspaper and provide solutions to correct the errors found. The method used in this study is descriptive qualitative. Data collection in this study was carried out by taking Suara Merdeka news published on October 11, 2024. The data source in this study was the Suara Merdeka online newspaper in the economic column in the MSME sector. The selected news was stored in text format in a word file so that analysis was easier to do. Errors were checked based on spelling categories according to EYD V rules. The findings of the error results were recorded regularly in a table, including the types of errors and their corrections. Data collection techniques include reading and recording the use of language in newspapers. The method applied in this study is a descriptive qualitative approach, with data collection techniques that include reading activities and recording the use of language in newspapers. The results of the October 11, 2024 edition of the study show that there are various types of language errors in newspapers. In the article entitled “National Tourism Has the Potential to Grow Regional MSMEs”, there were 5 spelling errors, 1 italic error, 2 syntax errors, 2 semantic errors, and 2 errors each in morphology and affixed words. These errors are generally caused by a lack of attention to the correct language rules according to EYD V.